Selection parameters for fruit yield and related traits in chilli (Capsicum annuum L.) - Yatung, Tasso; Dubey, Rakesh KR; Singh, Vikas; Upadhyay, Garima; Pandey, AK (Bangladesh Journal of Botany, 2015)
Thirty genotypes of chilli were evaluated in RBD with three replications at vegetable research farm, CHF, CAU, Pasighat, Arunachal Pradesh, India during kharif, 2011. Variability, correlation and path analysis were carried out to study the character association and contribution, respectively. Analysis of variance revealed significant differences among the genotypes for all traits. High PCV and GCV, heritability, genetic advance were observed for days to first flowering, plant height, number of seed per fruit, number of fruit per plant, ascorbic acid and fruit yield per plant. Correlation indicated that fruit yield per plant was positively and significantly correlated with number of branch per plant, number of fruit per plant and chlorophyll content while negative and significant association was established with ascorbic acid content. Maximum positive direct effect on fruit yield per plant was imposed by fruit weight, number of fruit per plant, number of seed per fruit and capsaicin content. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21600 Bangladesh J. Bot. 43(3): 283-291, 2014 (December)